New Technology User Liability for Data Loss and Damages - Katerina Dulčić (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Kotor, Montengero, 10-11 September 2015, 2015)
Information technology is spreading in all fields of our lives. We use new technologies for many purposes, but many of us are not willing to learn more than necessary basics. The author elaborates some of the legal cases that were discussed in courts, and that show the responsibility of the technology user for not applying essential security measures. Jurisprudence has determined that the level of security should be different for various types of data, depending on how sensitive information the subject is processing. It is hard, but needed, to elaborate the cost and benefit analysis in accordance for application of advanced information technology. Nevertheless, security of data could be expensive; it is always cheaper than damage reparation. The imminent risks are those of data loss and modification, but also of data steeling by interested subjects. New instruments give a great input in health and education services, but also the data they are elaborating are of great interest for predators, but also for data subjects. The use of cloud and grid technology is very productive for these fields, but, considering the risks, those should be used wisely and with great with. Goal of the paper is to examine the legal obligations of personal data storage in EU and general conditions of cloud storage services. The legal texts are going to be examined and analysed and correlated with legal obligations.
Keywords: K130; 330; Liability; Security measures for information technology; Data subject; Sensitive data; Grid technology; Cloud data storage